Pressure at stake: Swedish third graders’ talk about national tests in mathematics - Bagger, Anette (NOMAD Nordic Studies in Mathematics Education, 2016)
This article presents part of a larger scale ethnographic study1 about Swedish national tests in mathematics in the third grade. Indications concerning possible needs in the test situation are examined through 102 pupils’ talk about pressure and what is at stake. Results imply that this test could be experienced as a high stakes test. Negative pressure is quite common, especially among multilingual pupils in need of support and boys in need of support. There are gendered differences in the talk about what is at stake. The article frames who the pupil in need of support might be from a pupil’s perspective, but also discusses how these possible positions of need might be managed in practice.